Exopolysaccharides produced by lactic acid bacteria and Bifidobacteria: Structures, physiochemical functions and applications in the food industry. (September 2019) - Xu, Yuanmei; Cui, Yanlong; Yue, Fangfang; Liu, Lihua; Shan, Yuanyuan; Liu, Bianfang; Zhou, Yuan; Lü, Xin
Abstract: Exopolysaccharides (EPSs)-producing lactic acid bacteria (LAB) and Bifidobacteria are widely used as starter cultures to make fermented food products due to their technological benefits. Moreover, LAB-EPSs and bifido-EPSs have been demonstrated to possess various physiological functions such as antioxidant, anticancer, antibacterial and immunological activities, among which the immunoregulatory activity has attracted a lot of scientific interests in recent years. Generally, these functions are closely related to the chemical compositions and configurations of EPSs. This review sheds light on structures and functions of LAB-EPSs and bifido-EPSs. Among them, in vitro and in vivo models used to evaluate the immune effects of EPSs are summarized in detail, with particular emphasis on the structure-immunity relationship of EPSs. Furthermore, the applications of EPSs in the food industry, especially the different roles EPSs played in the yogurt texture, are discussed carefully in this review. Finally, some strategies of EPSs production are also proposed to provide some information about the enhancement of EPSs yield. Graphical abstract: Image 10167 Highlights: LAB-EPSs and bifido-EPSs have attracted a lot of scientific interests. Structures, functions and applications of LAB-EPSs and bifido-EPSs are presented in detail. Models for studying the immune effect of LAB-EPSs and bifido-EPSs are outlined. The structure-immunity relationship is discussed carefully. Roles of LAB-EPSs and bifido-EPSs played in the texture of yogurt are summarized.